A kind of phosphogypsum foamed building material and preparation method thereof
By combining phosphogypsum with lithium slag and manganese slag, and using specific foaming agents and water reducing agents, phosphogypsum foamed building materials with good mechanical properties are prepared, which solves the limitations of phosphogypsum in the application field and the ecological and environmental pressure problems, and achieves resource utilization and performance improvement.
Patent Information
- Application Number
- CN202411996988.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The complex composition of phosphogypsum has caused it to be unable to completely replace natural gypsum in many application fields, and its accumulated amount has increased year by year, causing ecological and environmental pressure.
By combining phosphogypsum with lithium slag and manganese slag, an alkaline gelling material system is constructed, and a specific foaming agent and water reducing agent are used to prepare phosphogypsum foamed building materials with good mechanical properties.
The resource utilization and large-scale utilization of phosphogypsum have been realized, and the resource utilization of lithium slag and manganese slag has been promoted. At the same time, the compressive strength and dry density of phosphogypsum foamed building materials have been improved, the water absorption rate has been reduced, and the thermal insulation performance has been enhanced.
Smart Images

Figure CN119774967A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a phosphogypsum foamed building material and a preparation method thereof. Background Art
[0002] Phosphogypsum is a solid waste produced in the wet phosphoric acid process, and its main component is calcium sulfate dihydrate. The composition of phosphogypsum is relatively complex. In addition to calcium sulfate, there are also incompletely decomposed phosphate ore, residual phosphoric acid, fluoride, acid insoluble matter, organic matter, etc. Among them, the presence of fluorine and organic matter has the greatest impact on the resource utilization of phosphogypsum. The random discharge and accumulation of phosphogypsum has seriously damaged the ecological environment, not only polluting groundwater resources, but also causing waste of land resources.
[0003] Although the current application of phosphogypsum involves many fields such as mine filling, building materials, and agriculture, its cumulative amount is still increasing year by year, and the pressure on the ecological environment is still severe. Due to its complex composition, it cannot completely replace natural gypsum in many application fields. Therefore, it is of great significance to develop new ways and methods for the resource and large-scale utilization of phosphogypsum. Summary of the invention
[0004] The object of the present invention is to provide a phosphogypsum foamed building material and a preparation method thereof. The present invention can not only recycle a large amount of phosphogypsum, but also promote the resource utilization of lithium slag and manganese slag, and can ensure that the foamed building material has good mechanical properties.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a phosphogypsum foamed building material, comprising the following preparation raw materials: phosphogypsum, waste slag, cement, a foaming agent, a water reducing agent and water; the waste slag is lithium slag and / or manganese slag;
[0007] Taking the total mass of the phosphogypsum, waste residue and cement as 100%, the mass of the phosphogypsum accounts for 20-40%, the mass of the waste residue accounts for 30-60%, and the mass of the cement accounts for 20-40%;
[0008] The mass of the foaming agent is 6-10% of the total mass of phosphogypsum, waste residue and cement;
[0009] The mass of the water reducing agent is 0.1-0.2% of the total mass of phosphogypsum, waste residue and cement;
[0010] The mass of the water is 20-30% of the total mass of the phosphogypsum, waste residue and cement.
[0011] Preferably, the foaming agent is composed of 0.1-1 wt% of an alkyl glycoside surfactant, 0.1-1 wt% of nano silicon dioxide, 0.05-1 wt% of methyl cellulose and the balance of water.
[0012] 3. The phosphogypsum foamed building material according to claim 1, characterized in that the water reducer is a polycarboxylic acid-based water reducer.
[0013] Preferably, the cement is 325 grade cement and / or 425 grade cement.
[0014] Preferably, the phosphogypsum foamed building material is a foamed block or a foamed wall.
[0015] Preferably, the median particle size of the waste residue is 2 to 25 μm.
[0016] Preferably, the 28-day compressive strength of the phosphogypsum foamed building material is 1-10 MPa, and the dry density is 700-1200 kg / m 3 .
[0017] The present invention provides a method for preparing the phosphogypsum foamed building material described in the above scheme, comprising the following steps: mixing phosphogypsum, waste residue and cement to obtain solid powder;
[0018] Mixing the solid powder with a water reducing agent and water to obtain a mixed slurry;
[0019] The foaming agent is made into foaming foam and injected into the mixed slurry, and stirred to obtain a foaming slurry;
[0020] Casting the foaming slurry into a shape to obtain a green sheet;
[0021] The green sheet is cured to obtain the phosphogypsum foamed building material.
[0022] Preferably, the curing temperature is 23±5° C., and the relative humidity is 50-90%; and the curing time is 14-28 days.
[0023] Preferably, the fluidity of the mixed slurry is 200-220 mm.
[0024] The invention provides a phosphogypsum foamed building material, comprising the following preparation raw materials: phosphogypsum, waste slag, cement, a foaming agent, a water reducing agent and water; the waste slag is lithium slag and / or manganese slag; taking the total mass of the phosphogypsum, waste slag and cement as 100%, the mass of the phosphogypsum accounts for 20-40%, the mass of the waste slag accounts for 30-60%, and the mass of the cement accounts for 20-40%; the mass of the foaming agent accounts for 6-10% of the total mass of the phosphogypsum, waste slag and cement; the mass of the water reducing agent accounts for 0.1-0.2% of the total mass of the phosphogypsum, waste slag and cement; and the mass of the water accounts for 20-30% of the total mass of the phosphogypsum, waste slag and cement.
[0025] Phosphogypsum is an acidic solid waste. The present invention can increase the pH of the matrix by compounding it with alkaline lithium slag and / or manganese slag, construct an alkaline gelling material system, and further improve the performance of the phosphogypsum matrix foamed building materials.
[0026] Furthermore, the foaming agent of the present invention is composed of 0.1-1wt% of alkyl glycoside surfactant, 0.1-1wt% of nano silicon dioxide, 0.05-1wt% of methyl cellulose and the balance of water, which can further improve the performance of phosphogypsum foamed building materials.
[0027] The results of the examples show that the compressive strength of the phosphogypsum foamed building material prepared by the present invention is 1-10 MPa and the dry density is 700-1200 kg / m 3 . BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 This is a photo of the phosphogypsum-lithium slag foamed building block prepared in Example 1;
[0029] Figure 2 This is a real photo of the phosphogypsum-manganese slag foamed building block prepared in Example 2. DETAILED DESCRIPTION
[0030] The invention provides a phosphogypsum foamed building material, comprising the following preparation raw materials: phosphogypsum, waste slag, cement, a foaming agent, a water reducing agent and water; the waste slag is lithium slag and / or manganese slag.
[0031] In the present invention, taking the total mass of the phosphogypsum, waste slag and cement as 100%, the mass of the phosphogypsum accounts for 20-40%, the mass of the waste slag accounts for 30-60%, and the mass of the cement accounts for 20-40%.
[0032] In a specific embodiment, the mass proportion of the phosphogypsum can be 20%, 25%, 30%, 35% or 40%; the mass proportion of the waste slag can be 30%, 35%, 40%, 45%, 50%, 55% or 60%; the mass proportion of the cement can be 20%, 25%, 30%, 35% or 40%.
[0033] The present invention has no special requirements on the source of the phosphogypsum, and any phosphogypsum from a source known in the art can be used. In the present invention, the median particle size of the phosphogypsum is preferably 5 to 20 μm; in a specific embodiment, it can be 5 μm, 8 μm, 10 μm, 15 μm, 17 μm or 20 μm.
[0034] In the present invention, the median particle size of the waste residue is preferably independently 2 to 25 μm; in a specific embodiment, it can be independently 2 μm, 5 μm, 10 μm, 15 μm, 20 μm or 25 μm. The present invention can increase the pH of the matrix and construct an alkaline gelling material system by compounding phosphogypsum with alkaline lithium slag and / or manganese slag, thereby improving the performance of phosphogypsum matrix foamed building materials.
[0035] In the present invention, the cement is preferably 325 grade cement and / or 425 grade cement.
[0036] In the present invention, the mass of the foaming agent is 6-10% of the total mass of phosphogypsum, waste slag and cement; in a specific embodiment, it can be 6%, 7%, 8%, 9% or 10%.
[0037] In the present invention, the foaming agent is preferably composed of 0.1-1wt% of an alkyl glycoside surfactant, 0.1-1wt% of nano silicon dioxide, 0.05-1wt% of methyl cellulose and the remainder of water. In a specific embodiment, the content of the alkyl glycoside surfactant in the foaming agent can be 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% or 1wt%; the content of the nano silicon dioxide in the foaming agent can be 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% or 1wt%; the content of the methyl cellulose in the foaming agent can be 0.05wt%, 0.1wt%, 0.2wt%, 0.4wt%, 0.6wt%, 0.8wt% or 1wt%.
[0038] The present invention has no special requirements for the preparation method of the foaming agent, and the components can be directly mixed evenly. The foam prepared by the foaming agent of the present invention has a small volume, but is more solid, dense, and has a high foaming efficiency.
[0039] In the present invention, the mass of the water reducer is 0.1-0.2% of the total mass of phosphogypsum, waste residue and cement; in a specific embodiment, it can be 0.1%, 0.15% or 0.2%. In the present invention, the water reducer is preferably a polycarboxylic acid water reducer. The polycarboxylic acid water reducer used in the present invention has high alkali water efficiency, low dosage and is easy to use.
[0040] In the present invention, the mass of the water is 20-30% of the total mass of the phosphogypsum, waste residue and cement; in a specific embodiment, it can be 20%, 23%, 26%, 28% or 30%.
[0041] In the present invention, the phosphogypsum foamed building material is preferably a foamed block or a foamed wall.
[0042] In the present invention, the 28-day compressive strength of the phosphogypsum foamed building material is preferably 1-10 MPa, more preferably 5-8 MPa; the dry density is preferably 700-1200 kg / m 3 , more preferably 800 to 1000 kg / m 3 .
[0043] The present invention provides a method for preparing the phosphogypsum foamed building material described in the above scheme, comprising the following steps: mixing phosphogypsum, waste residue and cement to obtain solid powder;
[0044] Mixing the solid powder with a water reducing agent and water to obtain a mixed slurry;
[0045] The foaming agent is made into foaming foam and injected into the mixed slurry, and stirred to obtain a foaming slurry;
[0046] Casting the foaming slurry into a shape to obtain a green sheet;
[0047] The green sheet is cured to obtain the phosphogypsum foamed building material.
[0048] The invention mixes phosphogypsum, waste residue and cement to obtain solid powder.
[0049] In the present invention, when the moisture content of the waste residue is greater than 10%, the waste residue is preferably dried at 60-105°C and then ball-milled. The median particle size of the waste residue after ball milling is 2-25 μm.
[0050] In the present invention, the phosphogypsum can be used directly after air drying without being subjected to heating treatment.
[0051] In the present invention, the mixing is preferably carried out in a mixer. The present invention has no special requirements on the mixing conditions as long as the phosphogypsum, waste residue and cement are mixed evenly.
[0052] After obtaining the solid powder, the present invention mixes the solid powder with a water reducing agent and water to obtain a mixed slurry.
[0053] In the present invention, the fluidity of the mixed slurry is preferably 200-220 mm, and those skilled in the art can adjust the amount of the water reducing agent within the range of 0.1-0.2% according to the fluidity requirements.
[0054] After the mixed slurry is obtained, the present invention injects the foaming agent into the mixed slurry to make foaming foam, and stirs to obtain the foaming slurry.
[0055] The present invention preferably uses a foaming machine to prepare the foaming agent into foam. The present invention has no special requirements for the stirring conditions, and it only needs to be stirred evenly.
[0056] After the foaming slurry is obtained, the present invention casts the foaming slurry into shape to obtain a green sheet.
[0057] In the present invention, the mold used for casting is preferably determined according to the purpose of the phosphogypsum foamed building material. When the phosphogypsum foamed building material is used as a foamed building block, the mold is a building block mold; when the phosphogypsum foamed building material is used as a foamed wall, the mold is a wall mold.
[0058] After obtaining the green sheet, the present invention cures the green sheet to obtain the phosphogypsum foamed building material.
[0059] In the present invention, the curing temperature is preferably 23±5°C, the relative humidity is preferably 50-90%, and the curing time is preferably 14-28 days. In a specific embodiment, the relative humidity of the curing can be 50%, 60%, 70%, 80% or 90%, and the curing time can be 14 days, 18 days, 20 days, 24 days or 28 days.
[0060] The phosphogypsum foamed building material and the preparation method thereof provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0061] Example 1
[0062] The phosphogypsum-lithium slag foamed blocks were prepared, and the material proportions were shown in Table 1.
[0063] The preparation method is:
[0064] Phosphogypsum (median diameter 8.66 μm), lithium slag (median particle diameter 22.5 μm) and cement (labeled P·O 42.5) were mixed in a mixer for 5 minutes to obtain a solid powder;
[0065] The solid powder is mixed with a solid high-efficiency polycarboxylic acid-based water reducer and water to obtain a mixed slurry having a fluidity of 220 mm;
[0066] A self-made nano foaming agent (whose composition is: 0.2wt% alkyl glycoside surfactant, 0.1wt% nano silicon dioxide foam stabilizer, 0.1wt% methyl cellulose enhancer, and the balance water) is foamed using a foaming machine, and the prepared foam is injected into the mixed slurry, and stirred evenly to obtain a foamed slurry;
[0067] Pouring the foaming slurry into a block mold to form a blank;
[0068] The green sheet is cured at a temperature of 23±5° C. and a relative humidity of 90% for 28 days to obtain a phosphogypsum-lithium slag foamed building block (such as Figure 1 shown).
[0069] Table 1 Example 1 Phosphogypsum-lithium slag foamed building block material ratio
[0070] Phosphogypsum Lithium slag cement Foaming agent Water reducing agent water 20% 40% 40% 8% 0.1% 20%
[0071] Note: In Table 1, the amount of phosphogypsum, lithium slag and cement is calculated by percentage based on the mass of solid powder materials; the amount of foaming agent, water reducing agent and water is also calculated by percentage based on the mass of solid powder materials. The same is true for the following Table 3.
[0072] Performance Test:
[0073] The performance test of the phosphogypsum-lithium slag foamed building block of Example 1 was carried out, and the test method referred to the relevant provisions in the national standard "Test Methods for Foamed Concrete and Products GB / T 43487-2023".
[0074] Compressive strength test method:
[0075] The specimen size is 100mm×100mm×100mm, and the number is 6. The specimen pressure area A is calculated, and the specimen is placed on the pressure plate of the testing machine, so that the center of the pressure plate of the testing machine coincides with the center of the specimen. The testing machine is started, and the load is applied until the specimen is destroyed. The failure load P is recorded, accurate to 10N, and the loading speed meets the requirements of the specification. The specimen compressive strength f = P / A, accurate to 0.01MPa.
[0076] Dry density test method:
[0077] The size of the specimen is 100mm×100mm×100mm, and there are 6 specimens. The size of the specimen is measured to an accuracy of 0.1mm, and the volume V of the specimen is calculated. The specimen is placed in an electric blast drying oven, and the temperature is raised to (105±2)℃ at a rate of 10℃ / h. It is dried to a constant mass at this temperature, and then moved to a dryer to cool to room temperature. The cooling time is not less than 24h. The criterion for constant mass is that the rate of change of the mass of the specimen measured twice at a constant temperature for 180min is less than 0.2%. Weigh the mass m of the specimen after drying to an accuracy of 0.1g. The dry density of the specimen is ρ=m / V×106, accurate to 1kg / m 3 .
[0078] Water absorption test method:
[0079] The size of the specimen is 100mm×100mm×100mm, and there are 6 specimens. The size of the test specimen is tested with an accuracy of 0.1mm, and the volume V of the specimen is calculated. The specimen is placed on the grid at the bottom of the constant temperature water tank. The distance between the specimen and the surrounding and the specimen should not be less than 25mm. Then place another grid on the upper surface of the specimen and add a pressure block. Add water with a temperature of (20±2)℃ to the water tank in 3 times. Add water to 1 / 3 of the specimen height for the first time and keep it for 24h. Add water to 2 / 3 of the specimen height for the second time. After 24h, add water to the specimen for the third time more than 25mm above the specimen and keep it for 120h. Take the specimen out of the water, place it on a wire mesh rack and drip water for 1min, then wipe off the water on the surface with a wrung wet cloth, weigh the mass m1 of each specimen in the saturated dry state, accurate to 0.1g, dry the specimen to a constant mass, and then move it to a drying room to cool to room temperature, and weigh its mass m2 after drying. The water absorption rate of the specimen is W = (m1-m2) / m2×100%, accurate to 0.1%.
[0080] Thermal conductivity test method:
[0081] The specimen size is 300mm×300mm×30mm, and the quantity is 2. The specimen size is tested. The specimen is dried to a constant mass. The thermal conductivity of the specimen is tested using a thermal conductivity meter according to the specification GB / T 10294. The result is accurate to 0.001W / (m·K).
[0082] The test results are shown in Table 2.
[0083] Table 2 Performance data of phosphogypsum-lithium slag foamed building blocks in Example 1
[0084] 28-day compressive strength (MPa) <![CDATA[Dry density (kg / m 3 )]]> Water absorption (%) Thermal conductivity (W / (m·K)) 5.31 1019 10.1 0.269
[0085] Example 2
[0086] Preparation of phosphogypsum-manganese slag foamed blocks (such as Figure 2 As shown), the material ratio is shown in Table 3;
[0087] The preparation method is the same as that of Example 1.
[0088] The performance of the phosphogypsum-manganese slag foamed building blocks was tested by referring to the test method of Example 1. The test results are shown in Table 4.
[0089] Table 3 Example 2 Phosphogypsum-manganese slag foamed block material ratio
[0090] Phosphate Manganese slag cement Foaming agent Water reducing agent water 30% 40% 30% 8% 0.1% 20%
[0091] Table 4 Performance data of phosphogypsum-manganese slag foamed building blocks in Example 2
[0092] 28-day compressive strength (MPa) <![CDATA[Dry density (kg / m 3 )]]> Water absorption (%) Thermal conductivity (W / (m·K)) 6.28 976 11.4 0.241
[0093] It can be seen from the above embodiments that the foamed building blocks prepared using phosphogypsum in the present invention have good mechanical properties, are light in weight, have low water absorption, and have good thermal insulation properties.
[0094] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A phosphogypsum foamed building material, characterized in that: The method comprises the following raw materials: phosphogypsum, waste slag, cement, foaming agent, water reducing agent and water; the waste slag is lithium slag and / or manganese slag; Taking the total mass of the phosphogypsum, waste residue and cement as 100%, the mass of the phosphogypsum accounts for 20-40%, the mass of the waste residue accounts for 30-60%, and the mass of the cement accounts for 20-40%; The mass of the foaming agent is 6-10% of the total mass of phosphogypsum, waste residue and cement; The mass of the water reducing agent is 0.1-0.2% of the total mass of phosphogypsum, waste residue and cement; The mass of the water is 20-30% of the total mass of the phosphogypsum, waste residue and cement.
2. The phosphogypsum foamed building material according to claim 1, characterized in that: The foaming agent is composed of 0.1-1 wt% of an alkyl glycoside surfactant, 0.1-1 wt% of nano silicon dioxide, 0.05-1 wt% of methyl cellulose and the balance of water.
3. The phosphogypsum foamed building material according to claim 1, characterized in that: The water reducing agent is a polycarboxylic acid water reducing agent.
4. The phosphogypsum foamed building material according to claim 1, characterized in that: The cement is 325 grade cement and / or 425 grade cement.
5. The phosphogypsum foamed building material according to claim 1, characterized in that: The phosphogypsum foamed building material is a foamed building block or a foamed wall.
6. The phosphogypsum foamed building material according to claim 1, characterized in that: The median particle size of the waste residue is 2 to 25 μm.
7. The phosphogypsum foamed building material according to any one of claims 1 to 6, characterized in that: The 28-day compressive strength of the phosphogypsum foamed building material is 1-10 MPa, and the dry density is 700-1200 kg / m 3 .
8. The method for preparing the phosphogypsum foamed building material according to any one of claims 1 to 7, characterized in that: The following steps are involved: mixing phosphogypsum, waste residue and cement to obtain solid powder; Mixing the solid powder with a water reducing agent and water to obtain a mixed slurry; The foaming agent is made into foaming foam and injected into the mixed slurry, and stirred to obtain a foaming slurry; Casting the foaming slurry into a shape to obtain a green sheet; The green sheet is cured to obtain the phosphogypsum foamed building material.
9. The preparation method according to claim 8, characterized in that: The curing temperature is 23±5° C., and the relative humidity is 50-90%; and the curing time is 14-28 days.
10. The preparation method according to claim 8, characterized in that: The fluidity of the mixed slurry is 200-220 mm.